The Construction of a Database with the Pupils of the Greek Catholic High School in Beiuș and the Geographic Visualization of their Birthplace (1876/1877 School Year) - HAIDUC, Alexandru-Augustin (Studia Universitatis Babeș-Bolyai Digitalia, 2021)
The article discusses the implementation of a database presenting the pupils that studied at the Greek Catholic High School in Beiuș in the 1876/1877 school year and presents a series of geographic annotations made on a map of the Habsburg Empire, opened in QGIS, consisting in the birthplaces of the aforementioned pupils. The database and the geographic annotations presented here are already being developed to include further pupils that studied at the Greek Catholic High School in Beiuș subsequent to the 1876/1877 school year. Therefore, the database and the geographic annotations are a pilot version of a broader project meant to conclude into a monograph regarding the Greek Catholic High School in Beiuș in the 19ᵗʰ century and first quarter of the 20ᵗʰ century.